Економічна характеристика поняття податкова безпека - Макарчук, Богдана Володимирівна; Makarchuk, Bohdana V. (My University, 2017)
Визначена роль податкової системи у розвитку економіки країни. Розкрита сутність податкової безпеки та наведені різні підходи до її визначення. Вказані основні податкові ризики та загрози податковій безпеці України. The role of the tax system in the development of the country's economy is determined. The essence of tax security is disclosed and various approaches to its definition are given. The main tax risks and threats to the tax security of Ukraine are indicated.
Economic characteristics of the definition of tax security
Keywords: податкова безпека; tax security; податкова система; tax system; податкові ризики; tax risks